BRIDGING CORPORATE VALUE: UNVEILING THE POWER OF COMPANY REPUTATION IN ESG SCORE IMPACT - sibarani, bintang (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
The purpose of this study was to determine the strength of the moderator variable (company reputation) on ESG score on corporate value. The sample is 79 companies going public on the Indonesia stock exchange in 2022. Linear regression used to test the variables, while to test the moderator variable using Process Hayes (2013). The findings demonstrated that the company's worth is significantly impacted by its ESG score. Then Company reputation at small values, moderator (W or Int_1) is low, attention to the ESG score may not be fully relevant or effective in explaining variations in the Corporate value. At low values of moderators, research expansion or more specific strategies may be required to understand other factors that may influence the relationship between the independent and dependent variables. At medium values, attention to ESG score tends to provide consistent or moderate results in explaining variation in corporate value. At medium values of moderators, more general or holistic research or strategies may be quite effective for understanding the relationship between the ESG score and corporate value the moderator variable strengthens the independent variable (ESG score), and finally at high values of the moderator, where the effect of the ESG score tends to be stronger or even increased. This interpretation suggests that under conditions or situations where the value of the moderator (W or Int_1) is high, attention to the ESG score may be particularly relevant and effective in explaining variations in the corporate value.